Osteocytic HIF-1α Pathway Manipulates Bone Micro-structure and Remodeling via Regulating Osteocyte Terminal Differentiation - Chen, Kaizhe; Zhao, Jian; Qiu, Minglong; Zhang, Lianfang; Yang, Kai; Chang, Leilei; Jia, Peng; Qi, Jin; Deng, Lianfu; Li, Changwei (Frontiers in Cell and Developmental Biology, 2022)
The activation of hypoxia-inducible factor 1α (HIF-1α) signaling has promising implications for the treatment of bone diseases such as osteoporosis and skeletal fractures. However, the effects of manipulating HIF-1α pathway on bone micro-structure and remodeling should be fully studied before the clinical application of therapeutics that interfere with the HIF-1α pathway. In this study, we found that osteocyte-specific HIF-1α pathway had critical role in manipulating bone mass accrual, bone material properties and micro-structures, including bone mineralization, bone collagen fiber formation, osteocyte/canalicular network, and bone remodeling. In addition, our results suggest that osteocyte-specific HIF-1α pathway regulates bone micro-structure and remodeling via impairing osteocyte differentiation and maturation.